2014
DOI: 10.1016/j.bbmt.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Outcomes of Human Leukocyte Antigen Matching by Allele-Level Typing in Adults with Acute Myeloid Leukemia Undergoing Umbilical Cord Blood Transplantation

Abstract: This retrospective study analyzed the impact of directional donor-recipient human leukocyte antigen (HLA) disparity using allele-level typing at HLA-A, -B, -C, and -DRB1 in 79 adults with acute myeloid leukemia (AML) who received single-unit umbilical cord blood (UCB) transplant at a single institution. With extended high-resolution HLA typing, the donor-recipient compatibility ranged from 2/8 to 8/8. HLA disparity showed no negative impact on nonrelapse mortality (NRM), graft-versus-host (GVH) disease or engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 28 publications
1
32
1
Order By: Relevance
“…3 Interestingly, recent analyses have also suggested an association between risk of relapse and degree of HLA mismatch. 6, 27, 28 In our report, the effect of HLA mismatch on the lower risk of relapse was independent of GVHD. This finding needs to be independently confirmed in larger numbers of patients…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…3 Interestingly, recent analyses have also suggested an association between risk of relapse and degree of HLA mismatch. 6, 27, 28 In our report, the effect of HLA mismatch on the lower risk of relapse was independent of GVHD. This finding needs to be independently confirmed in larger numbers of patients…”
Section: Discussionsupporting
confidence: 55%
“…36, 27, 28 Moreover, the negative impact of HLA-mismatch is, at least in part overcome by higher cell dose. 5 Other groups 27, 29 have recently shown that more HLA mismatch may be associated with better DFS in adults with AML in first remission and in children with hematological malignancy. However, a study of only adult patients showed similar risks of NRM, relapse and treatment failure for recipients of an adequately dosed single or a dUCB graft.…”
Section: Discussionmentioning
confidence: 99%
“…MDACC data have also shown increased TRM with increasing HLA-mismatch 38 . In contrast, a recent UMN analysis, for example, reported that a high degree of HLA-allele mismatch did not adversely affect transplant outcomes 39 , and such findings have also been reported in MSKCC and Spanish analyses 30,40 and the CTN propsective trial 23 . Notably, a subset analysis in the UMN study suggested recipients of dCB grafts with a 2–5/10 HLA-allele match were associated with a reduced risk of relapse in patients with acute leukemia 39 .…”
Section: Graft Selectionmentioning
confidence: 92%
“…26 Several studies have reported that higher donor-recipient HLA disparity in singleunit CBT for adult patients with leukemia decreased the risk of relapse, which translated to a survival benefit. 27,28 These reports indicated that a GVL effect could be present in patients after CBT. It is possible that the concentration of tacrolimus influenced the transplant outcome differently according to disease status before the transplantation; therefore, the optimal range of blood tacrolimus concentration early after CBT should be determined by balancing for GVHD prophylaxis and the effect of GVL.…”
Section: Discussionmentioning
confidence: 97%